2011
DOI: 10.1111/j.1365-2516.2010.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of hepatitis in boys with haemophilia associated with increased prevalence of obesity

Abstract: Hepatitis in children with haemophilia was historically most often associated with transfusion-transmitted infections. However, with the use of recombinant clotting factor concentrates, acquisition of such infections has now become rare. We studied the profile of hepatitis in North-American children with haemophilia in the modern era of safe blood products and excess childhood obesity. A total of 173 boys (<18 years) registered in the Pediatric Comprehensive Care Haemophilia Program were included in this retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…Three prevalence studies have arrived at discrepant findings on the relationship between haemophilia severity and BMI [6, 8, 19]. Revel-Vilk et al in a large cohort found that younger boys with severe haemophilia were more likely to be obese [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three prevalence studies have arrived at discrepant findings on the relationship between haemophilia severity and BMI [6, 8, 19]. Revel-Vilk et al in a large cohort found that younger boys with severe haemophilia were more likely to be obese [19].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only prevalence studies have examined the relationship between haemophilia disease severity and obesity with discrepant findings [6, 8, 19]. These studies have either had few participants or have been exclusively of pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with hemophilia are living longer and therefore are at risk for developing chronic conditions that may be further complicated by overweight/obesity [5, 6, 7, 8]. Emerging evidence makes the importance of obesity prevention clear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a 2011 Canadian study of boys under 18 years of age with hemophilia, the prevalence of obesity was increased for those with severe hemophilia compared to those with mild or moderate hemophilia [8]. Furthermore, when compared to Canadian population data, hemophilic boys who were 2–5 years old tended to have a higher prevalence of overweight and obesity compared to the age-matched Canadian population.…”
Section: Introductionmentioning
confidence: 99%
“…Revel-Vilk et al32 in Canada reported that overweight status and obesity are common among haemophilic boys, especially those who are younger and with more severe disease. As the use of prophylactic therapy was less common in younger boys, it is possible that the reduced activity among young boys affected their weight.…”
mentioning
confidence: 99%